STUDENTS FOREIGN LANGUAGE ANXIETY IN CLASSROOM-INTERACTIONS: A STUDY AT ENGLISH LANGUAGE STUDY PROGRAM UNIVERSITAS JAMBI - Adrefiza, Adrefiza (Universitas Muhammadiyah Metro, 2023)
This study investigates students' FLA in classroom interactions, why they felt anxious about speaking English, and how they coped with the anxiety. It also looks at a gender difference in the anxiety phenomenon and sees if females are more anxious than males in their interactions. The data were collected through electronic questionnaires to 100 selected students at the English Language Education Study Program (ELESP), Faculty of Education, Jambi University. Adapting the models from Zhiping and Paramasivam (2013) and Woodrow (2006), the results displayed three dominant factors contributing to students' English-speaking FLA, regardless of the gender aspect, were: (1) Fear of making errors or mistakes because of inadequate English mastery or proficiency (such as grammar, pronunciation, and vocabulary); (2) Fear of inability to create and organize ideas in English; and (3) Fear of having negative responses or corrections from the lecturers with the ratio of (73:71:64) respectively. There was a noticeable gender difference in the students' anxiety, where females were likely to be more anxious than males, with a ratio of (171:131). Pretending to do something such as reading or writing was the most frequent strategy by males and females in dealing with their anxiety. The lecturers were expected to respond to the students' FLA effectively and encourage them to do their best in the classroom.